Comunicarea managerială – factor al asigurării continuității între cicluri de învățământ superior [Articol] - Țurcanu, Carolina (CEP USM, 2019)
În articol pentru prima dată se încearcă a aborda problema privind comunicarea managerială din perspectiva realizării interconexiunii și continuității între cicluri de învățământ superior. Pornind de la analiza comunicării manageriale ca fenomen organizațional, a funcțiilor și demersurilor comunicării manageriale, sunt stabilite sursele și registrele acestui proces privind asigurarea integralității instituționale. Accentul a fost pus pe astfel de mecanisme, ca: informarea, transmiterea deciziilor, motivarea cadrelor manageriale și didactice, realizarea feedback-ului etc.

In the given article we try to address the problem of managerial communication from the perspective of achieving the interconnection and continuity between cycles of higher education for the first time. Starting from the analysis of managerial communication as an organizational phenomenon, only the sources and registers of this process regarding the assurance of institutional integrity are established. Emphasis has been placed on such mechanisms as: informing, transmitting decisions, motivating management and teaching staff, conducting feedback, etc.
MANAGERIAL COMMUNICATION – A FACTOR OF ENSSURING CONTINUITY BETWEEN HIGHER EDUCATION CYCLES
Keywords: comunicare managerială; tipuri de comunicare; managerial communication